STRATEGIC PRINCIPLES OF ADAPTIVE DEVELOPMENT FOR DOMESTIC ENTERPRISES IN THE CONTEXT OF THE CIRCULAR ECONOMY AND MILITARY CHALLENGES - Khalina, Olena; Boyarchuk, Serhiy (Current Problems of Sustainable Development, 2026)
The article examines the strategic foundations of adaptive development of Ukrainian enterprises under the conditions of circular economy formation and wartime challenges. The relevance of the study is determined by the growing instability of the business environment, the disruption of logistics and production links, the shortage of resources, the increase in operational risks, and the need for enterprises to maintain continuity of activity despite crisis transformations. It is substantiated that the traditional linear model of value creation, based on the sequential use of resources from extraction and production to consumption and waste generation, becomes increasingly vulnerable in wartime conditions. Such a model intensifies dependence on primary raw materials, external suppliers, energy stability, and uninterrupted logistics, which reduces the flexibility and resilience of enterprises. The purpose of the article is to substantiate the strategic directions of adaptive development of enterprises through the transformation of linear value chains into an adaptive-circular model capable of strengthening resource efficiency, resource autonomy, and long-term competitiveness. The study reveals the importance of circular economy principles as a practical mechanism for overcoming resource constraints, reducing waste, extending the life cycle of products, reusing materials, developing repair and recovery processes, reverse logistics, eco-design, and reintegrating secondary resources into production. The proposed adaptive-circular model allows circular economy to be considered not only as an environmentally oriented concept, but also as a strategic tool for ensuring enterprise resilience under conditions of uncertainty, deficit, and wartime shocks. Particular attention is paid to the adaptive closure of resource cycles, which makes it possible to create internal resource reserves, reduce dependence on unstable external supplies, minimize logistics risks, and support the continuity of production processes. The article also emphasizes the importance of cooperation between the defense-industrial complex and enterprises of civilian sectors, especially in the context of technology transfer, dissemination of engineering solutions, development of repair and recovery capacities, and implementation of resource-efficient management practices. It is argued that state support plays a significant role in creating institutional, regulatory, and financial conditions for the transition of enterprises to circular business models. The practical significance of the study lies in substantiating an approach that can be used to strengthen the adaptability, resource security, and competitiveness of Ukrainian enterprises during wartime instability and in the process of post-war economic recovery.
Keywords: adaptive development of enterprises; circular economy; wartime challenges; resource autonomy; adaptive-circular model; post-war recovery